Video Planning the Role of Women for Improving the Economy in the Family During the COVID-19 Pandemic in Cigugur Girang Village - Salsabila, Nisrina; Karlina, Nichi Hana; Setiawan, Diwan; Ichsan, Banon Gilang Muhamad Kali (International Journal of Ethno-Sciences and Education Research, 2023)
In general, men serve as the backbone to provide for the family. However, one of the consequences of the Covid-19 Pandemic was that husbands who worked to earn a living were suddenly forced to leave, resulting in widespread unemployment and decreased enthusiasm for life. To resolve this issue, women in Cigugur Girang Village, Bandung Regency, try to contribute to the improvement of their families' economies by developing Micro, Small, and Medium Enterprises (MSME). This will be documented in the form of a testimonial videography design. The design of this video progresses through the creative process in the order of the preliminary plan process, including research, needs analysis, goal setting, target audience selection, and creative concept selection. The pre-production stage consists of determining the storyline and characters, and creating story boards. The production phase includes video capturing, video and audio editing, consulting with supervisors, rendering, then the video is distributed on Youtube. In this testimonial video, women from Cigugur Girang Village in Bandung Regency describe their experiences starting and growing MSME businesses. The design of this video testimonial can be used as an alternative form of media to inspire and motivate other women in the same situation to contribute to the improvement of their family economy.